Two cases of acute anterolateral compartment syndrome following inversion ankle injuries. (December 2020) - Bango, Jugert; Zhang, Evan; Aaron, Daniel L.; Diwan, Amna
Abstract: Introduction: Compartment syndrome is a limb threatening, and sometimes life-threatening medical condition. It usually occurs in high energy lower extremity injuries, commonly in the younger patient with classic signs and symptoms. Pain out of proportion to exam is one of the key elements in diagnosis. A high vigilance for signs and symptoms of this condition should be present on most physicians' radars who treat emergency conditions, as this case report demonstrates, the mechanism and story are not always classic. Presentation of cases: Two cases of young, healthy adults who underwent fasciotomy for compartment release for compartment syndrome isolated to the anterolateral compartment, but who did not sustain a high energy trauma, but rather a twisting ankle injury. Conclusion: Compartment syndrome can occur in young, healthy, active patients with a lower energy twisting injury and without fracture. A high level of suspicion on the clinicians' part will prevent adverse outcomes to the patient.